The converso's return: conversion and Sephardi history in contemporary literature and culture - Kandiyoti, Dalia (Stanford Studies in Jewish History and Culture Ser., 2020)
"The Converso's Return is a study of recent fiction and memoirs by U.S. Latinx, Spanish, French, and Turkish authors about the current revival of Iberian Jewish history, in particular, the largely forced conversions of Jews to Catholicism in fourteenth- and fifteenth-century Spain and Portugal. This seemingly remote history has been the topic of a substantial library of contemporary literary and popular writing, especially since the 1992 quincentennial commemorations of the 1492 conversions and expulsion of Jews and Muslims from Spain and the conquest of the Americas. The recent claiming of Sephardi converso ancestry by Christian (and to a much lesser extent Muslim) descendants in the Americas, Europe, and Turkey has taken place simultaneously with the fictional and testimonial writing about conversos and their descendants by authors on several continents. What is it about conversos that has sparked their imagination? What do we learn and rethink about conversions' afterlives including their resurgence in the present, and how does this help us understand how and why we return to and resuscitate the past? The literary writing in English, Spanish, French, and Turkish about the fate of the converts through the centuries that The Converso's Return investigates together help us complicate ideas about conversos, contemporary historical consciousness, the role of genealogy in culture, collective memory, missing/imagined archives, Sephardi identities, and world literature"--.